Banksy Urban art in a material world - Blanché, Ulrich (Tectum Wissenschaftsverlag, 2016)
Bristol born Banksy is usually categorized as a Street Artist, although his art, in content and form, transcends a narrow understanding of this term. This publication primarily deals with Banksy as a contemporary Urban Artist and his relationship with consumer culture. It examines Banksy not only in light of his illicit work on the street, but also in regard to his gallery exhibitions. The study highlights representative works of his art, pieces which demonstrate his versatility, but also stand for different periods of his oeuvre. This book presents the first academic study of Banksy's art in English; with a history and discussion of the terms Graffiti, Street Art and Urban Art and a rich array of biographical information. It will be of interest to academics and the general public as well.